PENGEMBANGAN MODUL PEMBELAJARAN MATA KULIAH JARINGAN KOMPUTER BERBASIS CISCO PACKET TRACER DI JURUSAN TEKNIK INFORMATIKA DAN KOMPUTER FAKULTAS TEKNIK UNIVERSITAS NEGERI MAKASSAR. - Hendrawansyah; Mustari Lamada; Hendra jaya (UNM Journal of Technology and Vocational, 2022)
The objectives of this study (1) are to develop a learning module for a Cisco Packet Tracer-based computer network course in the Department of Informatics and Computer Engineering, Faculty of Engineering, State University of Makassar. (2) To produce a valid learning module in the computer network course at the Department of Informatics and Computer Engineering, Faculty of Engineering,Makassar State University. (3) To produce practical learning modules in the Computer network course at the Department of Informatics and Computer Engineering, Faculty of Engineering, Makassar State University. (4) To produce an effective learning module in the computer network course at the Department of Informatics and Computer Engineering, Faculty of Engineering, Makassar StateUniversity. The type of research used is research and development (Research and Development) which aims to develop and produce a product. The development procedure refers to the ADDIE development model. The result obtained is the development of the learning module for the computer network course. The research instrument used an assessment sheet according to 2 expert lecturers and 30 student responses. The results of the validity of the module material are 89% in the "very valid" category, the module design validity 90% in the "very valid" category, the practicality of the module by the validator 90% in the "very practical" category, student responses 84% in the "very valid" category, the practicality of the module by students 84 % category "very practical" and the effectiveness of the module68% category "effective".